From 2, 6‐Dichloronicotinic Acid to Thiopeptide Cores. Issue 28 (22nd August 2013) - Just‐Baringo, Xavier; Albericio, Fernando; Álvarez, Mercedes
Abstract: The scope of 2, 6‐dichloronicotinic acid as a precursor of thiopeptide polyheterocylic cores has been extensively studied in a cross‐coupling‐based approach. Differentiation of the two chlorinated positions under SN Ar conditions and versatility of the carboxylic acid are key for the preparation of 2, 3, 6‐trisubstituted pyridines with complete regiocontrol. With the present strategy, nine different azole‐substituted pyridines were synthesized. Studies towards the selective deprotection of their functionalities resulted in a set of fully orthogonal protecting groups that permits the elongation of all three pyridine substituents. Abstract : The polyheterocyclic cores of thiopeptides can be accessed from 2, 6‐dichloronicotinic acid in a regioselective and modular fashion by using a palladium catalyzed cross‐coupling strategy.